INVENTARISASI JENIS SERANGGA TANAH DI KAWASAN TAMAN WISATA ALAM KERANDANGAN DALAM UPAYA PENYUSUNAN BAHAN AJAR EKOLOGI - Ni Made Wirastini; Iwan Doddy Dharmawibawa; Sucika Armiani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2016)
ABSTRACT: Kerwa Nature Park (TWA) Kerandangan is one of the tropical forest area on the island of Lombok and has been designated as a conservation area since June 1, 1992. As a conservation area TWA Kerandangan has a high diversity of insect species. The diversity of these insects can be used as bioindicator of environmental stability in TWA Kerandangan. This study aims to identify soil insects, as well as to know the diversity of insects in the TWA Kerandangan area. This research was conducted at TWA Kerandangan and insect identification was done at Biology Laboratory of FPMIPA IKIP Mataram in June 2016. This research was conducted by using Pitfall trap technique in two different location that is on flat land and bumpy land and at two time different in the morning and evening. Result of research on TWA Kerandangan obtained 5 species of insects namely Empoasca fabae, Camponotus modoc, Myrmecocystus mexicanus, Asemoplus montanus and Gryllus spyang total of 124 individuals. The values of the diversity index (H ') for the Empoasca fabaeyaitu species were 0.038, Camponotus modoc0,161, Myrmecocystus mexicanus0,213, Asemoplus montanus0,066 and Gryllus sp 0.175. The highest diversity index value is found in Myrmecocystus mexicanus species and the lowest diversity index value is found in Empoasca fabae species.